2022
DOI: 10.1002/brb3.2696
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in rTMS treatment response: A deep learning‐based EEG investigation

Abstract: Introduction The present study aimed to investigate sex differences in response to repetitive transcranial magnetic stimulation (rTMS) in Major Depressive Disorder (MDD) patients. Identifying the factors that mediate treatment response to rTMS in MDD patients can guide clinicians to administer more appropriate, reliable, and personalized interventions. Methods In this paper, we developed a novel pipeline based on convolutional LSTM‐based deep learning (DL) to classify 25 female and 25 male patients based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Furthermore, the research cited herein 45 showed that male brains responded significantly better to repetitive transcranial magnetic stimulation (rTMS) than female brains in patients with severe depression. Meanwhile, the sensitivity of the trigeminal nerve to pain is also different, 59 women are more susceptible to pain than men.…”
Section: Affect Factors Of Brain Sex Dimorphismmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, the research cited herein 45 showed that male brains responded significantly better to repetitive transcranial magnetic stimulation (rTMS) than female brains in patients with severe depression. Meanwhile, the sensitivity of the trigeminal nerve to pain is also different, 59 women are more susceptible to pain than men.…”
Section: Affect Factors Of Brain Sex Dimorphismmentioning
confidence: 96%
“…Male rats with an activated defecation center in the brain and spinal cord have an increased motility response to the colon, but it has no effect on the colon of female rats. Furthermore, the research cited herein 45 showed that male brains responded significantly better to repetitive transcranial magnetic stimulation (rTMS) than female brains in patients with severe depression. Meanwhile, the sensitivity of the trigeminal nerve to pain is also different, 59 women are more susceptible to pain than men.…”
Section: Characteristics Of Brain Sexual Dimorphismmentioning
confidence: 96%
See 1 more Smart Citation
“…Measures of connectivity, asymmetry across hemispheres, and power in frontal and temporal electrodes are predictive of treatment response to antidepressant medication as well as to repetitive transcranial magnetic stimulation (rTMS) (Watts et al, 2022). Applying deep learning, treatment response to rTMS was predicted with accuracies over 90% (Adamson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Alpha asymmetry in patients with MDD has been found to be associated with different antidepressant medications in a sex-specific manner, even after controlling for potential confounders such as sex and age (Arns et al 2016). Furthermore, a recent study employing a novel deep learning pipeline to classify patients' response to TMS found that TMS affects depression differently based on sex (Adamson et al 2022). Hence, it is plausible that factors associated with sex exert an influence on treatment outcomes.…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%